The Transformation of Traditional Lecture into Constructional Lecture in the Interactive Environment - Pečeliūnaitė, Angelė (Acta Paedagogica Vilnensia, 2016)
The article analyses ways and means how to improve the level of professional computer literacy of students in arts studies. When traditional teaching methods are applied to Information Technologies, they prove to be ineffective. With regard to arts students, the author created a new teaching method which enables the student to work in virtual environment from the initial stage. The student immediately has to explore the virtual environment, learn how to work with it and use it to satisfy his/her needs. The teaching model is based on an electronic programme which analyses computer-based text-processing methods. On the basis of a survey, the article analyses students’ readiness to work in interactive changeable virtual environment and their evaluations of the teaching model. The analysis shows that most students find the teaching model attractive and acceptable. After the course students not only gain valuable knowledge but also considerably improve their level of professional computer literacy, overcome computer-phobia, enhance their self-confidence. The course motivates students to acquire new knowledge and makes them open to innovations.